Deficits in Emotion Recognition and Theory of Mind in Parkinson’s Disease Patients With and Without Cognitive Impairments - Dodich, Alessandra; Funghi, Giulia; Meli, Claudia; Pennacchio, Maria; Longo, Chiara; Malaguti, Maria Chiara; Di Giacopo, Raffaella; Zappini, Francesca; Turella, Luca; Papagno, Costanza (Frontiers in Psychology, 2022)
Background: Emotion recognition and social deficits have been previously reported in Parkinson’s Disease (PD). However, the extent of these impairments is still unclear and social cognition is excluded from the cognitive domains considered in the current criteria for PD mild cognitive impairment (MCI). This study aims to analyze emotion recognition, affective and cognitive theory of mind in early PD patients classified according to Level II MCI criteria, and to evaluate the prevalence of socio-cognitive deficits in this sample. Methods: We enrolled 45 participants with PD, classified as cognitively unimpaired (CU; n=32) or MCI (n=13) based on a standard neuropsychological assessment. Social cognitive skills were evaluated through validated tests for emotion recognition (i.e., Ekman 60-faces test, Ek60 Test) and mental states attribution (Story-based Empathy Task, SET) and compared to a group of 45 healthy controls (HC). Between-group differences in social tasks were performed, as well as correlation analyses to assess the relationship between social, cognitive, and clinical variables. Finally, the number of patients with social cognitive impairments in both MCI and CU subgroups was computed based on Italian normative data. Results: Statistical comparison revealed significant differences among groups in the Ek60 test, with MCI obtaining significantly lower scores than HC and CU, especially for negative emotions. Significant differences were detected also in the SET, with lower performance in emotion and intention attribution for both PD groups compared to HC. A significant correlation emerged between the Ek60 test and emotion attribution. Nine patients showed poor performance at social tasks, 5 of them being classified as PD-CU. Discussion: PD's cognitive profile was characterized by emotion recognition and attribution deficits. These results, as well as the detection of CU patients with isolated socio-cognitive impairments, underline the importance of assessing social cognition in PD as a possible early marker of cognitive decline.